Elemental Forensic Analysis of Glass - Rodríguez, Mariela (2007)
At identifying glass as forensic evidence, there is a continued move away from dependence on physical properties measured, such as index of refraction and density, towards methods of elemental analysis of its traces. Several spectroscopic, radiochemical and mass spectrometry techniques have been applied for multielemental analysis of small samples of glass. This review shows some of the most commonly used methods, as well as their advantages and limitations.